'Plumb line scribe': Using multimedia to preserve traditional craft skills. Issue 1 (1st February 2013) - Lassen, Ulrik Hjort; Wood, Nicola
The skills required in craft practice involve a high degree of tacit knowledge which is frequently difficult for the craft expert to articulate. Nicola Wood, a multimedia designer, has undertaken extensive research over the last ten years seeking to understand the knowledge of skilled craftsmen and find methods of capturing and passing it on. She has developed an elicitation strategy that employs an expert learner to uncover the skilled knowledge of master craftsmen, and a transmission strategy based on the concept of bridges to assist the design of learning resources for novices. Ulrik H. Lassen has used the techniques developed by Wood to record and transmit the skilled knowledge needed to make timber-framed buildings, knowledge that today is in danger of being lost. The focus of the study has been the procedure for scribing timbers, which is a central part of the building process. The aim of the research was to investigate the possibility of combining the two roles defined in Wood's research as an expert learner and designer. Being a skilled carpenter, Lassen has acted as an expert learner, learning the skills of scribing through a combination of researching existing documentation, working with master craftsmen and his own experimentation. At the same time, he developed and tested a multimedia learning resource to provide 'bridges' for new learners to this knowledge. The outcome of the application of Wood's elicitation and transmission strategy to plumb line scribing is a demonstration of the transferability of Wood's methods within this new context. This is important because it reveals the potential for other craft practitioners to apply Wood's methods to their own learning and teaching, and produce learning resources to provide bridges to their craft knowledge and preserve their unique skills.